The implementation of TT Vaccine as a Marriage Administrative Requirement in KUA Palengaan District: a Maslahah Mursalah Perspective - Shohibul Hidayat; Urwatul Wusqo (Khuluqiyya: Jurnal Kajian Hukum dan Studi Islam, 2026)
This study examines the implementation of Tetanus Toxoid (TT) immunization as an administrative prerequisite for marriage registration at the Office of Religious Affairs (KUA) of Palengaan District through the perspective of maslahah mursalah. It also explores how the policy is understood and implemented by the local community. This research employs a descriptive qualitative field study with sociological and normative approaches. Primary data were collected through interviews with the Head of KUA Palengaan, KUA staff, healthcare workers at the Palengaan Community Health Center, and prospective brides and grooms. Secondary data were obtained from official documents, relevant regulations, fiqh literature, journals, and previous studies. The findings reveal that TT immunization is frequently perceived merely as an administrative requirement, while its broader health benefits remain insufficiently understood. Limited public health literacy and inadequate dissemination of information contribute to this perception. From the perspective of maslahah mursalah, the TT immunization policy embodies significant public benefits, particularly in protecting life (hifz al-nafs) and reducing health risks for mothers and newborns. However, a gap persists between the normative objectives of the policy and its practical implementation. This study contributes to the discourse on integrating public health policies with Islamic legal principles and highlights the need for enhanced education, public awareness, and intersectoral coordination to improve policy effectiveness.